Electrolytic Cleaning and Regenerative Therapy of Peri-implantitis in the Esthetic Area: A Case Report - Gianfreda, Francesco; Punzo, Andrea; Pistilli, Valeria; Bollero, Patrizio; Cervino, Gabriele; D'Amico, Cesare; Cairo, Francesco; Cicciù, Marco (European Journal of Dentistry, 2022)
Implantology represents the gold standard in oral rehabilitation. Unfortunately, a new pathology begins to show itself to clinicians that no longer affects only and solely the supporting tissues of the tooth but also dental implants and peri-implantitis. In this study, we present a case report regarding a tissue regeneration maneuver involving dental implants. The clinical and radiographic results are encouraging, regarding the use of these techniques on implant surfaces. Surely, the advent of new biomaterials and surgical techniques will make this practice safe and predictable.
Keywords: guided tissue regeneration; periodontics; oral surgery; peri-implantitis